Relationship between screen time, sleep duration, parent-child interaction and psychosocial adjustment among preschool children in Selangor, Malaysia - Foo, Ning; Ismail, Nellie; Arshat, Zarinah (Canadian Center of Science and Education (CCSE), 2022)
The current study aimed to determine the relationship between screen time, sleep duration, parent-child interaction and psychosocial adjustment among preschool children in Selangor, Malaysia. The study also intended to assess whether difference exists in psychosocial adjustment between male and female, examine whether sleep duration and parent-child interaction mediate the relationship between screen time and psychosocial adjustment as well as explore on unique predictors of psychosocial adjustment. Multistage cluster sampling method was employed to select the sample in the study. The sample consisted of 392 parents (either mother or father) of preschool children aged between four to six years old in Selangor, Malaysia. Screen Time Questionnaire (STQ) was applied to measure screen time while the Children’s Sleep Habits Questionnaire (CSHQ) was used to assess sleep duration. Besides, the Parent-Child Interaction Checklist and the Strengths and Difficulties Questionnaire (SDQ) were utilized to evaluate parent-child interaction and psychosocial adjustment respectively. Findings demonstrated that there was a significant difference in psychosocial adjustment in terms of hyperactivity, peer problems, prosocial behaviour, and total difficulties between boys and girls. Besides, screen time significantly correlated with parent-child interaction. Results also revealed that child’s gender, father’s years of education, child calming screen time, and parent-child interaction significantly predicted psychosocial adjustment. However, mediation analysis was unable to be conducted to test the mediating role of sleep duration and parent-child interaction on the relationship between screen time and psychosocial adjustment, as screen time did not correlate significantly with psychosocial adjustment in overall.